Online sales and business model innovation in art markets: a case study - Fernandes, A.; Afonso, L. (Social Sciences, 2020)
Every year online sales represent a higher percentage of the sales total in nearly all sectors of the economy, and the art markets are no exception. However, there are few empirical studies showing how online sales and digital technologies are transforming the art markets at a micro-level. This study is based on the detailed examination of the financial performance of one of the two largest Portuguese auction houses, Cabral Moncada Leilões (CML), over a period of twelve years (2007-2018), complemented with interviews with its top-managers. It analyses a set of financial indicators (e.g., EBIT, ROA, EQUITY, sales volume, net results, etc.), along with some markers that are specific to the auction sector (e.g., average lot value, number of auctions per year, etc.). From this analysis it is possible to conclude that the deterioration of this company's financial performance was the driving force that led it to explore the potential of digital economy. In the process, its business model changed dramatically, leading the company to a different market position and to the enlargement of its national and international customer base.